Numerical Simulation of the Thermo-catalytic Reforming Process: Up-scaling Study - Elmously, Mohamed; Neidel, Johannes; Apfelbacher, Andreas; Daschner, Robert; Hornung, Andreas (Industrial & Engineering Chemistry Research, 2021)
The up-scaling of the pyrolysis technologies is the next step to achieve the industrial scale and to fulfill the energy and petrochemical demand in large-scale units. The overall goal of this study is to up-scale the Thermo-Catalytic Reforming (TCR) technology from the laboratory to the pilot unit. In the previous part of the study, the up-scaling was studied experimentally in regard to the product yields and qualities. Therefore, a computational fluid dynamics (CFD) study is carried out to investigate the effects of up-scaling of the TCR system on the temperature distribution through the intermediate pyrolysis and the catalytic reforming process. A multifluid model and K-ϵ model are employed to simulate the TCR process for the mixture flow of sewage sludge as a solid phase and pyrolysis vapor as a gas phase. The results reveal a CFD model that can predict the heat distribution and flow velocities through the TCR system, while the deviations between simulation data and experimental work are considered small. The errors in the maximum biomass temperature within the auger reactor are 0.0 and 4.2% for TCR2 and TCR30, and the deviations in the solid residence time are about 0.8 and 0.74 s, respectively. Furthermore, the deviations in the vapor residence time within the post-reformer are 0.35 and 0.81 s for TCR2 and TCR30, respectively. Additionally, the CFD model provides a good platform for further simulation of the chemical reaction kinetics.
CRIS-Team Scopus Importer:2021-04-16